(untitled) (Journal of the College of Basic Education, 2023)
This study is an attempt to investigate the effect of using concept mapping as a prewriting strategy on Iraqi EFL college students’ achievement in essay writing. To fulfill the aims of the study, the researcher has adopted two null hypotheses. The first states that there is no statistically significant difference between the achievement mean scores of the students who are taught essay writing through concept mapping as a pre-writing strategy and those who are taught essay writing through the conventional way. The second hypothesis states that there is no statistically significant difference between the experimental group students’ achievement mean scores in the organization, content and quality of expressions in the pre and posttests. To achieve the aim of the study, a ten-week experiment was conducted using the pretest-posttest non-equivalent groups design. Two groups of 105 students were selected from the population of third year students/College of Education for Women-Department of English during the academic year (2013-2014). One group was selected as the experimental group (namely section B) and another group was selected as the control group (namely section C). Both students of the experimental and control groups were exposed to pre and posttests. Using the t-test for two independent samples, it is found that there is a statistically significant difference in favour of the experimental group; whereas, by using t-test for two dependent samples, it is found out that there is a significant development in the experimental group students’ achievement in organization, content and style and quality of expression. This indicates that using concept mapping as a prewriting strategy is more effective than the presentation- practice- production teaching or the Lecture Method teaching. Conclusions, recommendations and suggestions for further studies are put forward.